Cement Incidentally Exposed to Fire and Its Impact on the Compressive Strength of Concrete - Robert Ataria; John TrustGod; Abel Brayai (Advances in Civil Engineering and Environmental Science)
This study examined the effects of fire exposure on limestone cement and its impact on the compressive strength of concrete. Portland limestone cement graded at 42.5N was subjected to 150, 300, 450, and 600 °C temperatures. At each temperature, samples were removed after 15, 30, 45, and 60 minutes of exposure, then cooled before use. The heating setup included a furnace, an oven pot, an air blower, and a thermometer. A total of 48 concrete cubes were prepared for each exposure condition, along with 12 control cubes made with unexposed cement. Concrete was mixed in a 1:2:4 ratio with a water-to-cement ratio of 0.55, then cured and tested for compressive strength at 7, 14, 21, and 28 days. An analysis of variance (ANOVA) was conducted to evaluate the results and the relevance of the experimental data. Findings showed that fire exposure significantly reduced cement performance, with notable strength losses at higher temperatures. After 60 minutes at 300 °C, the 7-day compressive strength dropped from 16 MPa to 8 MPa. A pronounced decline was observed at 600 °C, where the 28-day strength decreased by 25%. Extended exposure durations further lowered strength. Despite this, fire-exposed cement achieved compressive strengths ranging from 5 MPa to 20 MPa.